Hubungan Lingkar Perut dengan Volume Testis pada Mahasiswa Kedokteran - Karema, Vivian B.; Marunduh, Sylvia R.; Sapulete, Ivonny M. (Medical Scope Journal, 2025)
Abstract: Male infertility is a growing global issue, with obesity contributing to decreased fertility by affecting endocrine function and sex hormone regulation, which can reduce testicular volume. Lack of physical activity and excessive fast food consumption lead to obesity among university students. Abdominal circumference is a key parameter of central obesity. This study aimed to obtain the relationship between abdominal circumference and testicular volume in medical students of Universitas Sam Ratulangi, Manado. This was an analytical and observational study with a cross-sectional design. Purposive sampling was employed, and 52 students participated in this study. Data were collected using a measuring tape and a Prader orchidometer. The Spearman correlation test was applied with a significance level of 0.05. The results showed that the average abdominal circumference of the 52 participants was 88.57±14.15 cm. The average left testicular volume was 19.04±3.89 ml, and the right testicular volume was 19.29±3.84 ml. The Spearman correlation test showed a significant negative relationship between abdominal circumference with both left (p=0.018; r=-0.327) and right (p=0.038; r=-0.289) testicular volume. In conclusion, there is a weak negative correlation exists between abdominal circumference and testicular volume, indicating that larger abdominal circumference is associated with smaller testicular volume in these students. Keywords: abdominal circumference; testicular volume; fertility Abstrak: Infertilitas pria telah menjadi masalah global, dengan obesitas berkontribusi terhadap penurunan kesuburan. Obesitas memengaruhi fungsi endokrin dan regulasi hormon seks, yang dapat menurunkan volume testis. Kurangnya aktivitas fisik dan konsumsi makanan siap saji menyebabkan obesitas pada mahasiswa. Lingkar perut merupakan parameter obesitas sentral. Penelitian ini bertujuan mengetahui hubungan lingkar perut dengan volume testis pada mahasiswa kedokteran Universitas Sam Ratulangi Manado. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Pengambilan sampel dilakukan secara purposif, dan didapatkan 52 mahasiswa sebagai partisipan. Data dikumpulkan dengan menggunakan pita pengukur dan Prader Orchidometer. Uji korelasi Spearman diterapkan dengan tingkat signifikansi 0,05. Hasil penelitian mendapatkan rerata lingkar perut 88,57±14,15 cm. Rerata volume testis kiri 19,04±3,89 ml dan rerata volume testis kanan 19,29±3,84 ml. Hasil uji korelasi Spearman mendapatkan hubungan bermakna dengan korelasi negatif antara lingkar perut dengan volume testis kiri (p=0,018; r=-0,327), dan dengan volume testis kanan (p=0,038; r=-0,289). Simpulan penelitian ini ialah terdapat hubungan bermakna antara lingkar perut dengan volume testis, dengan nilai korelasi negatif lemah. Semakin besar lingkar perut maka semakin kecil volume testis. Kata kunci: lingkar perut; volume testis; kesuburan